Correlation of clinical severity criteria of coronavirus infection with laboratory changes in patients vaccinated against Covid 19 - Akhrarova Aziza Rakhmatullaevna; Kdirbaeva Perizat Zoldasbaevna (Genius Journals, 2022)
The pandemic caused by coronavirus infection remains one of the major health problems and poses a serious threat to the entire planet. Currently, active vaccination against the new type of coronavirus infection continues in the Russian Federation, as in all countries. Vaccination is an important component of a comprehensive program for the prevention and control of COVID-19. Mass vaccination of the population can prevent both access to care and hospitalization in high-incidence settings with COVID-19, thereby reducing the burden on the health care system. Despite the ongoing challenges in the fight against the pandemic caused by SARS-^V-2, to date vaccination is the most effective way to protect against this infection. In the context of the urgent approval of the use of vaccines against the new coronavirus infection, the changing epidemiological situation and the wide variety of different types of vaccines used, clinical trials of the effectiveness of various preventive vaccines in different regions of the world are very large. according to As the pandemic progresses, all countries will need to address new challenges, such as the weakening of vaccine protection, the emergence of new strains of SARS-CoV-2, and the need for other preventive measures to prevent disease. will need updated information. the impact of the pandemic
Keywords: Coronavirus infection; COVID-19; vaccination; Contemporary questions of pediatrics.